PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HIGHER ORDER THINKING SKILLS PESERTA DIDIK PADA MATERI EKOSISTEM - Merliyana Saragih; Syarifah Widya Ulfa; Ummi Nur Afinni Dwi Jayanti (Jurnal Bionatural, 2024)
Through the application of the Problem Based Learning (PBL) learning model, it can improve students' problem-solving abilities and become an appropriate innovation for learning at SMA Negeri 2 Torgamba, especially in Biology learning on ecosystem concepts, which will really help students to observe and understand. Using the Problem Based Learning (PBL) model as a learning model is better than the conventional learning model used. In the experimental class, the level of Higher Order Thinking Skills (HOTS) of students before the Problem Based Learning learning model was implemented was still relatively low, but when it was implemented there were significant changes. Meanwhile, in the control class using conventional learning models it is still relatively low. Based on the results and discussion, the results of hypothesis testing assisted by SPSS version 22 software have obtained a Sig value. (2-tailed) α (0.001 0.005), so Ho is rejected and H1 is accepted. This indicates that there is a significant difference in posttest averages between the experimental and control classes. The difference in the average posttest score obtained by the experimental class was 76.13 and the average score for the control class was 60.83. It can be concluded that there is an influence of the problem based learning (PBL) model on the higher order thinking skills (HOTS) of SMA Negeri 2 Torgamba students on ecosystem material